High Temperature Disrupts Organelle Distribution and Functions Affecting Meiotic Maturation in Porcine Oocytes - Lee, Song-Hee; Sun, Ming-Hong; Zhou, Dongjie; Jiang, Wen-Jie; Li, Xiao-Han; Heo, Geun; Cui, Xiang-Shun (Frontiers in Cell and Developmental Biology, 2022)
Heat stress (HS) has been known to cause reproductive failure in animals, especially in summer. HS severely affects the developmental potential of oocytes and leads to low fertility rates. Previous studies have reported that HS compromises embryo development in bovine oocytes, and reduces ovarian development in mice, thereby impairing reproductive function in animals. However, the effect of high temperature (HT) on the organelles of porcine oocytes is unknown. In this study, we reported that exposure to HT for 24 h (41°C) significantly decreased meiotic maturation in porcine oocytes (p < 0.05). Further experiments on organelles found that HT induced mitochondrial dysfunction, increased abnormal mitochondrial distribution, and decreased mitochondrial membrane potential (MMP). We also found that HT induced abnormal endoplasmic reticulum (ER) distribution and higher expression of glucose regulatory protein 78 (GRP78), suggesting that HT exposure induces ER stress. Our results also indicated that exposure to HT induced abnormal distribution and dysfunction of the Golgi apparatus, which resulted from a decrease in the expression of the vesicle transporter, Ras-related protein Rab-11A (RAB11A). In addition, we found that HT exposure led to lysosomal damage by increasing the expression of lysosome-associated membrane protein 2 (LAMP2) and microtubule-associated protein 1A/1B-light chain 3 (LC3). In summary, our study revealed that HT exposure disrupts organelle dynamics, which further leads to the failure of meiotic maturation in porcine oocytes.